Epigenetic hallmarks of age-related macular degeneration are recapitulated in a photosensitive mouse model. (21st July 2020) - Luu, Jennings; Kallestad, Les; Hoang, Thanh; Lewandowski, Dominik; Dong, Zhiqian; Blackshaw, Seth; Palczewski, Krzysztof
Abstract: Age-related macular degeneration (AMD) is a chronic, multifactorial disorder and a leading cause of blindness in the elderly. Characterized by progressive photoreceptor degeneration in the central retina, disease progression involves epigenetic changes in chromatin accessibility resulting from environmental exposures and chronic stress. Here, we report that a photosensitive mouse model of acute stress-induced photoreceptor degeneration recapitulates the epigenetic hallmarks of human AMD. Global epigenomic profiling was accomplished by employing an Assay for Transposase-Accessible Chromatin using Sequencing (ATAC-Seq), which revealed an association between decreased chromatin accessibility and stress-induced photoreceptor cell death in our mouse model. The epigenomic changes induced by light damage include reduced euchromatin and increased heterochromatin abundance, resulting in transcriptional and translational dysregulation that ultimately drives photoreceptor apoptosis and an inflammatory reactive gliosis in the retina. Of particular interest, pharmacological inhibition of histone deacetylase 11 (HDAC11) and suppressor of variegation 3–9 homolog 2 (SUV39H2), key histone-modifying enzymes involved in promoting reduced chromatin accessibility, ameliorated light damage in our mouse model, supporting a causal link between decreased chromatin accessibility and photoreceptor degeneration, thereby elucidating a potential new therapeutic strategy to combat AMD.